Residential Water Consumption Monitoring System Using IoT and MQTT Communication - Villacís-Guerrero, Jacqueline del Pilar (2022)
Water shortage across the globe causes changes in the life of the human being, not to mention that water is a resource that must be preserved for future generations. The companies that distribute and charge fees for residential water services have problems performing the periodical manual readings. Thus, showcasing inaccuracy in the costumer statements at the end of every month. The following paper describes the development process of a low-cost intelligent control and monitoring system of residential water consumption. The system design uses a flow sensor that measures the influx of liquid as it passes through the pipes. Based on the value that the conventional meter marks at the beginning of the day, it is possible to determine the daily consumption. The processing of acquired data is performed with a low-cost controller (SBC). Also, the respective control actions were transmitted towards a solenoid valve, which controls the passage of water to the house. Next, an access and communication point is established applying bidirectional MQTT (Message Queue Telemetry Transport) protocol to send and receive data wirelessly through Internet of Things (IoT). Data was stored and managed on a local server. The prototype displays information through an LCD screen and in a web page. To achieve this, the server sends information such as date-time, username, meter number, etc. The results showcase that the measurements were performed as expected. Thus, validating the possibility of using it in a larger sample